Economic, Accounting, and English Language Literacy as the Foundation of Student Competitiveness in the Global Labor Market - Martina, Sri; Purba, Djuli Sjafei (Universitas Pahlawan Tuanku Tambusai, 2026)
The competitiveness of higher education graduates in the global labor market is no longer determined solely by academic achievement, but increasingly by the mastery of multidimensional literacy aligned with international industry demands. In response to this shift, this study investigates the role of economic literacy, accounting literacy, and English language proficiency as strategic foundations for enhancing students’ employability and professional competitiveness at the global level. This study adopts a qualitative literature review approach with descriptive analysis. Data were collected from Google Scholar and other reputable academic databases by reviewing scholarly publications released between 2010 and 2026. An initial pool of 70 articles was identified, from which 50 studies were selected through a systematic screening process based on relevance to the research focus, methodological quality, and the significance of their findings. The analysis reveals that economic literacy, accounting literacy, and English proficiency are closely interconnected and should not be developed in isolation. A lack of integrated literacy development contributes to skill mismatch, weak analytical abilities in contextual economic and financial situations, and limited professional communication skills among graduates in global workplace settings. Furthermore, evidence from case studies indicates that insufficient mastery of these integrated literacies often becomes a critical barrier in recruitment processes and professional performance within multinational companies. Based on these findings, this study emphasizes the importance of cross-disciplinary curriculum integration in higher education. It also recommends the implementation of project-based learning, global simulation activities, and strengthened collaboration between higher education institutions and international industries as sustainable strategies to enhance graduate competitiveness and better prepare students for the challenges of the global labor market.